Exploring the anti-allergic property of potentized sodium chloride using nasal eosinophil count as a criterion - Dania P Johnson; K John Paul (Wolters Kluwer Medknow Publications, 2019)
Background: Nasal eosinophilia is a specific and valuable means for diagnosing and predicting the prognosis of allergic rhinitis (AR). Evidence-based recommendation for treating AR with homeopathic medicines is lacking. Symptomatology of Natrum Muriaticum (NM) derived from homeopathic pathogenetic trials and clinical proving aids its wide use in practice. Objective: The study aided in ascertaining the anti-allergic property of NM in lowering the nasal eosinophil count in patients with AR. Methods: This prospective, observational study included patients diagnosed with AR along with nasal eosinophilia, provided they received NM 30C homeopathic remedy. Written consent was obtained from 15 patients and then included in the study. Nasal smear was collected on the first visit before the treatment and at the end of 2 weeks after the treatment. Statistical Analysis and Results: Pre- and post-treatment nasal eosinophil counts were statistically analyzed using the paired t-test. The difference in mean eosinophil count (0.06333) was statistically significant, where P < 0.00000085. Results: From the study conducted, the eosinophil count was recorded before and after treatment [Figure 1]. Out of 15 participants, two had moderate eosinophilia and 13 had mild eosinophilia before treatment. There was no eosinophilia in any of the patients in the 2nd week after NM intake. Conclusions: It was evident that NM lowers the nasal eosinophil count when administered according to homeopathic principles. Nevertheless, it has opened new avenues to investigate the underlying mechanisms of the anti-allergic property possessed by NM through in vitro studies.